My five senses stage 1 - Aliki (China: Harper Collins Publisher Inc., 1989)
"My Five Senses" is an educational book designed to teach young readers about the five senses: sight, hearing, taste, touch, and smell. Through simple language and engaging illustrations, the book explains how each sense works and how they help people explore and understand the world around them. It introduces children to the concept that each sense has a unique role$1 (Bsight allows us to see, hearing helps us listen, taste lets us enjoy food, touch helps us feel textures, and smell lets us identify scents. The book encourages children to become more aware of their senses in everyday life, fostering curiosity and helping them understand how their bodies interact with the environment.s
This book is a beginner's guide to the five senses, designed for young children. It uses simple language and colorful illustrations to explain how each sense$1 (Bsight, hearing, taste, touch, and smell$1 (Bhelps us experience and navigate the world around us. Ideal for early childhood education, the book introduces fundamental concepts in a fun and interactive way, encouraging children to observe and explore their own sensory experiences. "My Five Senses" is a valuable resource for parents and educators to promote sensory awareness and foster curiosity in young learners.s
Keywords: Senses; Human Body